Dampak Stress Kerja Tenaga Pelayanan Sosial Terhadap Pelayanan bagi Warga Binaan Sosial (Studi kasus pada PSAA Putra Utama 3 Tebet Jakarta) - Fitriyah, Fitriyah; Febriana, Agata Terra (UI Scholars Hub, 2022)
Social service workers have an important role in the process of the delivery of services to the children who lived in social institutions. However, an excessive workload implicates work stress which causes an impact on service delivery. This study aims to describe the stress faced by social service workers concurrently with social workers and the impact on services at PSAA Putra Utama 3 Tebet. This study used qualitative descriptive research from October 2019 until January 2020. The data is being collected using in-depth interviews and observations method. The subject of this research is social service officers, WBS, and the leader of PSAA. Thus, the results showed that social service workers concurrently with social workers lead to stress due to the heavy workload. This caused the services where the workers are being less friendly to colleagues and WBS. They were also unable to establish intense communication with parents/guardians. Often, the workers postpone the assessment process and the report making for the WBS development, In addition, sometimes the workers are being passive towards the problems faced by WBS.